Clinical Potential of Extracellular Vesicles in Type 2 Diabetes - Liu, Jie (Front Endocrinol (Lausanne), 2021)
Type 2 diabetes (T2D) is a major public health disease which is increased in incidence and prevalence throughout the whole world. Insulin resistance (IR) in peripheral tissues and insufficient pancreatic β-cell mass and function have been recognized as primary mechanisms in the pathogenesis of T2D, while recently, systemic chronic inflammation resulting from obesity and a sedentary lifestyle has also gained considerable attention in T2D progression. Nowadays, accumulating evidence has revealed extracellular vesicles (EVs) as critical mediators promoting the pathogenesis of T2D. They can also be used in the diagnosis and treatment of T2D and its complications. In this review, we briefly introduce the basic concepts of EVs and their potential roles in the pathogenesis of T2D. Then, we discuss their diagnostic and therapeutic potentials in T2D and its complications, hoping to open new prospects for the management of T2D.